Full-wave intravascular ultrasound simulation from histology - Kraft, Silvan; Conjeti, Sailesh; Noël, Peter B.; Carlier, Stéphane; Navab, Nassir; Katouzian, Amin (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2014)
In this paper, we introduce a framework for simulating intravascular ultrasound (IVUS) images and radiofrequency (RF) signals from histology image counterparts. We modeled the wave propagation through the Westervelt equation, which is solved explicitly with a finite differences scheme in polar coordinates by taking into account attenuation and non-linear effects. Our results demonstrate good correlation for textural and spectral information driven from simulated IVUS data in contrast to real data, acquired with single-element mechanically rotating 40 MHz transducer, as ground truth. © 2014 Springer International Publishing.
CRIS-Team Scopus Importer:2023-03-08